2018
DOI: 10.1111/mmi.14109
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Candida glabrata Pdr1 by the deubiquitinase subunit Bre5 occurs in a ubiquitin independent manner

Abstract: The primary route for development of azole resistance in the fungal pathogen Candida glabrata is acquisition of a point mutation in the PDR1 gene. This locus encodes a transcription factor that upon mutation drives high level expression of a range of genes including the ATP-binding cassette transporter-encoding gene CDR1. Pdr1 activity is also elevated in cells that lack the mitochondrial genome (ρ cells), with associated high expression of CDR1 driving azole resistance. To gain insight into the mechanisms con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…When driven from the MET3 promoter, GOF forms accumulated to a lower level than the wild-type protein yet target gene transcription was higher. Our previous data have indicated that the Bre5 protein appears to be a negative regulator of Pdr1 levels in C. glabrata and strains lacking Bre5 accumulated higher levels of Pdr1 than wild-type cells [15]. Additionally, GOF forms of Pdr1 were degraded at a faster rate than the wild-type protein [10].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…When driven from the MET3 promoter, GOF forms accumulated to a lower level than the wild-type protein yet target gene transcription was higher. Our previous data have indicated that the Bre5 protein appears to be a negative regulator of Pdr1 levels in C. glabrata and strains lacking Bre5 accumulated higher levels of Pdr1 than wild-type cells [15]. Additionally, GOF forms of Pdr1 were degraded at a faster rate than the wild-type protein [10].…”
Section: Discussionmentioning
confidence: 95%
“…Our previous data have indicated that the Bre5 protein appears to be a negative regulator of Pdr1 levels in C . glabrata and strains lacking Bre5 accumulated higher levels of Pdr1 than wild-type cells [ 15 ]. Additionally, GOF forms of Pdr1 were degraded at a faster rate than the wild-type protein [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting of C. glabrata whole-cell protein extracts was performed as previously described (42), and extracts were prepared using NaOH/β-mercaptoethanol-based lysis. All Western blot experiments were performed in triplicate, and the results were quantitated using Odyssey software and are presented as averages of these determinations with standard errors.…”
Section: Methodsmentioning
confidence: 99%